Correction: Short Report: Early genomic detection of SARS-CoV-2 P.1 variant in Northeast Brazil. - Stephane Tosta; Marta Giovanetti; Vanessa Brandão Nardy; Luciana Reboredo de Oliveira da Silva; Marcela Kelly Astete Gómez; Jaqueline Gomes Lima; Cristiane Wanderley Cardoso; Tarcisio Oliveira Silva; Marcia São Pedro Leal de Souza; Pedro Henrique Presta Dias; Vagner Fonseca; Tulio de Oliveira; et al. (Public Library of Science (PLoS), 2022)
[This corrects the article DOI: 10.1371/journal.pntd.0009591.].